Effect of Sales, Current Ratio, Debt to Assets Ratio and Company Size on Company Profitability - Umalasita - Dewi; Dody - Setyadi; Suwardi - Suwardi (Politeknik Negeri Semarang, 2022)
This research was based on the issues of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX), namely the decline in profitability for the period 2017-2021. This research aims to examine the effect of the independent variables is Sales, Current Ratio (CR), Debt to Assets Ratio (DAR), and Firm Size on Profitability. The sample in this research were 14 property and real estate companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period which were selected using the purposive sampling method. The data analyzed used is 70 data (14 companies in 5 years of observation). Analysis model used in this research was multiple linear regression panel data analysis using Eviews 9.0. The results of the multiple linear regression analysis of panel data show that (1) the effect of sales on profitability is significant (2) the effect of the current ratio (CR) on profitability is not significant (3) the effect of debt to assets ratio (DAR) on profitability is not significant (4) The effect of firm size on profitability is significant